2020
DOI: 10.21034/iwp.41
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are Marriage-Related Taxes and Social Security Benefits Holding Back Female Labor Supply?

Abstract: In the U.S., both taxes and old age Social Security benefits depend on one's marital status and tend to discourage the labor supply of the secondary earner. To what extent are these provisions holding back female labor supply?We estimate a rich life-cycle model of labor supply and savings for couples and singles using the Method of Simulated Moments (MSM) on the 1945 and 1955 birth-year cohorts and we use it to evaluate what would happen without these provisions. Our model matches well the life cycle profiles … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Our paper also contributes to the literature that estimates statistical representations of individual earnings. 10 There are three ways prior studies have recovered income processes: (1) fitting statistical models of the earnings processes using GMM (e.g., Storesletten et al (2004), Karahan and Ozkan (2013), Guvenen et al (2015)), (2) fitting structural models of earnings processes using simulated method of moments (e.g., Blundell et al (2008), Guvenen and Smith (2014), and Madera ( 2016)), and (3) using Bayesian methods to estimate individual specific earnings processes (Geweke and Keane (2000), Jensen and Shore (2011), Nakata and Tonetti (2015), Gu and Koenker (2017), Borella, De Nardi, and Yang (2019) and Chatterjee, Morley, and Singh (2021)). 11 The first two methods do not allow researchers to recover realized shocks person-by-person, while the Bayesian methods, which encompass the filter presented in this paper, do.…”
mentioning
confidence: 99%
“…Our paper also contributes to the literature that estimates statistical representations of individual earnings. 10 There are three ways prior studies have recovered income processes: (1) fitting statistical models of the earnings processes using GMM (e.g., Storesletten et al (2004), Karahan and Ozkan (2013), Guvenen et al (2015)), (2) fitting structural models of earnings processes using simulated method of moments (e.g., Blundell et al (2008), Guvenen and Smith (2014), and Madera ( 2016)), and (3) using Bayesian methods to estimate individual specific earnings processes (Geweke and Keane (2000), Jensen and Shore (2011), Nakata and Tonetti (2015), Gu and Koenker (2017), Borella, De Nardi, and Yang (2019) and Chatterjee, Morley, and Singh (2021)). 11 The first two methods do not allow researchers to recover realized shocks person-by-person, while the Bayesian methods, which encompass the filter presented in this paper, do.…”
mentioning
confidence: 99%
“…There are a number of promising avenues along which to extend our framework. The first would be to introduce marriage and spousal benefits, as in Sánchez-Marcos and Bethencourt (2018), Nishiyama (2019) and Borella et al (2019). A second is to consider the entire tax and transfer system, rather than just Social Security.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also have implications for analyses of retirement benefits' potential impact on households' retirement decisions. Recent studies evaluating the potential impact of reducing or eliminating spousal or survivor benefits (Knapp 2014;Borella et al 2019;Nishiyama 2019) using structural models of household decision-making assume that potential income sources are treated equally. In the context of own, spousal, and survivor retirement benefits, our findings suggest that this is not true.…”
Section: Discussionmentioning
confidence: 99%
“…Nishiyama (2019), who focuses on the redistributive mechanism between singles to couples within pension systems, provides evidence that survivor and spousal benefits reduce female labor market participation by around 1.5% in the U.S. Similarly, Borella, De Nardi, and Yang, (2019) found that eliminating U.S.…”
Section: Institutional Details Of Germanymentioning
confidence: 99%